Al-Sheikh Dr. Muhammad Idris al-Marbawi's contribution to Islamic studies in the Malay World - Muhamad Shukri, Abdul Salam (IIUM Press, International Islamic University Malaysia, 2020)
Al-Sheikh Dr. Muhammad Idris bin 'Abd al-Ra'uf al-Marbawi al-Azhari al-Malayuwi (1893-1989) gained prominence in the Malay world with his Arab-Malay Dictionary called Qamus Idris al-Marbawi. He also wrote a translation and commentary on Sunan al-Tirmidhi called Bahr al-madhi, and is responsible for numerous literary works. His contributions to Islamic studies enriched the Muslim academia in Malaysia and Muslim world in general. Al-Marbawi was concerned with knowledge of language. He wanted the Malays to be proficient in Arabic in order to study Islam. One way to help them is by compiling an Arabic-Malay dictionary. After putting all effort and energy to study Arabic language from many great literatures, he finally succeeded. He managed to arrange different types of dictionaries.